<span>Given the two end of the diameter of the circle, we are able to compute the center of the circle as 0.5*[(-1,3)+(7,-7)]=(3,-2). The radius of the circle is 0.5*sqrt[(-1-7)^2+(3+7)^2]=sqrt(41). Therefore the equation of the circle is (x-3)^2+(y+2)^2=41.</span>
Y=35(0.35) is exponential decay
Answer:
x=16
y=-6
Step-by-step explanation:
Answer:
1 sandal= $7
1 flip flop =$2.5
Step-by-step explanation:
say one sandal costs x and one flip flop costs y
3 x+y=23.50
4x+2y=33
solve using simultaneous equationsto find the values of x and y